Recovery of deceased scuba divers from within flooded subterranean caves - Buzzacott, Peter; Nelson, C.; Hill, K.; Hires, L. (Elsevier Ireland Ltd, 2017)
© 2017 Elsevier B.V. Each year in the US three divers, on average, perish inside flooded caves and their remains require recovery. Recovery is a hazardous undertaking often performed by members of the International Underwater Cave Rescue and Recovery (IUCRR) team, in collaboration with local law enforcement and medical examiners/coroners. Since forming in 1999 the IUCRR have established standard recovery procedures for cave diving fatalities. This article reviews each stage of the recovery; the call out, arrival on site, the search, recording/preserving the evidence, the recovery, the handover and post-recovery record-keeping. A series of five cases highlight the challenges IUCRR divers are trained to face. It is strongly recommended local dive teams do not attempt to recover bodies from within flooded caves. IUCRR divers are trained to utilize a uniform procedure that is acceptable to the local law enforcement Incident Command System.